Mass communication skills through the language of discourse (Arabic satellite channels as a model) (Journal of the College of Basic Education, 2022)
Language is the realistic and sensitive basis for every communication between two or more parties. It is an important link that prepares the meanings and encodes them according to a linguistic structure governed by agreed-upon rules that everyone communicates and coexists with.Whereas the forms of communication are: personal, mediative, and public. None of them can move away from language in its dealings and communication patterns. Since each of them has its own characteristics and skills, it must be launched in its fields through verbal and non-verbal symbols and wear the elements and elements of the influential language according to the intended goal.Thus, it makes the recipient the imam of two things: Either he is unable to understand these symbols, and the purpose of them fails, or he meditates and indulges simply and energetically, so that it matches what the communicator wants.